ANALISIS KEJADIAN STEAM GENERATOR TUBE RUPTURE (SGTR) BERDASARKAN SKENARIO MIHAMA UNIT 2 - Ekariansyah, Andi Sofrany; Widodo, Surip (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2015)
On February 9,1991, a Steam Generator Tube Rupture (SGTR) took place at the Mihama Unit No. 2. From that event, the accident sequence representing the actuation of protection system and engineered safety feature to mitigate the leak from primary system to secondary system is recorded. That sequence is then applied on the Japanese standard PWR to be simulated using RELAP5/SCDAP/Mod3.2 thermal-hydraulic code. The purpose is to compare consequences resulted if this accident is occurred on the Japanese standard PWR. Parameter compared are break mass flow, fluctuation of primary and secondary pressure, and fluctuation of pressurizer level. The simulation result shown that the difference in the time duration from the initiation of rupture up to the leak termination, which takes place in shorter duration on the standard Japanese PWR. It is also shown that the total amount of the primary coolant leaked through the break nozzle to the secondary system that calculated is bigger than on the Mihama unit 2. The character of break mass flow, fluctuation of the primary system and level of pressurizer is slightly different in the beginning of the event, but is in similar trend in the end of event as the break flow is terminated. The simulation result also shows the necessity of operator action to manually isolate the auxiliary feedwater system in the affected steam generator, to actuate the main steam relief valves in the intact steam generator, and to actuate the auxiliary spray and power operated relief valve on pressurizer to anticipate the event as part of the emergency operating procedures.